Improving training methods by means of dynamic systems research background - Torrents, C.; Balagué, N. (International Journal of Computer Science in Sport, 2002)
Some of the deficiencies of training methods come probably nowadays from the influence of the computer metaphor, the model of lineal causality (stimulus-effect) and the division of the human being into parts. Research is also based on this approach and new technologies appear that try to improve each component or each part of the training plan independently. Some examples can be cited to illustrate the previous statement: